Patient Perceptions of FDA Approval: Gaps in Education or Variation in Values?. Issue 4 (August 2021) - Ford, Paul J.; Fox, Robert J.; Mercer, Mary Beth; Cofield, Stacey S.
Abstract : Objective: To assess perceptions and opinions about the Food and Drug Administration (FDA) approval process for disease-modifying therapies (DMT) in people living with multiple sclerosis (MS). Methods: People living with MS were invited to complete a web-based survey of their perceptions of the FDA role and process for approval of MS medications. The survey asked about the role of the FDA, factors involved in the approval process, which voices should represent those with MS in deliberations about drug approval, and the level of comfort with uncertain safety of newly approved therapies. Results: Three thousand thirty-three respondents met inclusion criteria for data analysis. Most respondents seemed to understand the role of the FDA, although only half understood a fundamental FDA role: balancing the risks and benefits when considering drug approval. Significant differences were observed in many areas between those who have and have not tried DMTs. Comfort with uncertainty was associated with several factors relating to side effects and benefits believed important for the FDA to consider. Most respondents reported that people who participated in the medication's clinical trial were particularly able to represent people living with MS. Conclusion: Perceptions regarding the FDA and views of who should represent people living with MS varied between those who have and have not tried DMT. There is variability in personal values that should be recognized and taken into account when considering regulatory responsibilities. Interventions are needed to address educational gaps regarding the mission and trustworthiness of the FDA as an oversight body.